Student Creativity in Art Learning Through Batik Jumputan Activities at SMP Negeri 52 Surabaya - sarah salsabila; Setyo Yanuartuti (Jurnal Pendidikan Sendratasik, 2026)
This study aims to describe the creativity of eighth-grade students of SMP Negeri 52 Surabaya in art learning through batik jumputan activities. Creativity is examined using the 4P model proposed by Rhodes (1961), encompassing Person (individual student characteristics), Press (learning environment), Process (creative process), and Product (creative output). Employing a qualitative descriptive approach, data were collected through passive participatory observation across ten sessions, semi-structured interviews with the Art and Culture teacher and eighth-grade students, and documentation including activity photographs and student artworks. Analysis followed the interactive model of Miles and Huberman, with source and method triangulation ensuring data validity. Findings indicate that: (1) students demonstrated high interest in practical art activities, with motivation and self-confidence developing gradually through direct creative experience; (2) outdoor learning settings created a conducive atmosphere for creative exploration, supported by the teacher's facilitative role, productive peer interaction, and adequate school facilities; (3) students' creative processes unfolded through preparation, technique and color exploration, technical problem-solving, and culminated in the emotionally meaningful illumination moment of unveiling tied fabrics; (4) each group produced artworks with unique and original motifs and color combinations, with measurable creative development across all ten sessions. The study concludes that batik jumputan activities effectively support comprehensive creativity development across all four dimensions of the 4P model.